Desain Angkringan Sebuah Resiliensi Saat Pandemi Covid-19: (Studi Kasus : Angkringan Temu Rasa, Celuk Gianyar Bali) - Utami, Ni Kadek Yuni; Trisna, Ni Made Sri Wahyuni (Program Studi Desain Interior Unikom, 2023)
The use of outdoor space as resilience during a pandemic seems to answer the community's need for social interaction when regulations apply to social-physical restrictions in carrying out activities. Angkringan as a place to eat outside began to appear a lot during the Covid-19 pandemic situation by offering affordable food prices, simple design places and other adjustments that follow health protocol rules. This makes people interested in visiting and spending time in these places. This research was conducted with the aim of analyzing the design of angkringan as resilience during a pandemic. In addition, this research can also provide insight to interior designers or architects on the use of outdoor space during a pandemic and serve as a guide during an endemic. The collection method was carried out by distributing questionnaires to 100 visitor respondents angkringan and observation to angkringan Temu Rasa in the parking area of ​​the Cening Ayu Souvenir Center, Sukawati, Gianyar. Observations emphasize the efforts made by the management to create a comfortable and safe outdoor space during a pandemic. Observation data will be compared with the results of people's preferences for angkringan during a pandemic. By using relevant theory, it is hoped that through this research the design resilience efforts can be identified which include layout, circulation, materials, furniture carried out in the design.angkringan to answer the need for outdoor space that is safe, comfortable, and in accordance with health protocols.